The Palestinian agricultural sector: deepening dependency and the failure of international development aid - Halbert, Nicole (AUC Knowledge Fountain, 2012)
This research details how development aid to the Palestinian agricultural sector not only fails to foster Palestinian self-sufficiency. It demonstrates how this aid buttresses a system of economic interconnection wherein Palestinian agriculture is dependent both on Israeli materials and cooperation, and on international funding for agricultural development projects. This research relies on a breadth of past academic analyses and fieldwork conducted in Palestine in October, 2011. This research concludes that, for development aid to be effective in building greater Palestinian sovereignty, it should be focused on economic sectors that are more independent of Israeli control.